Review: Indonesian Herbal Ingredients as Immune Booster - Yasmiwar Susilawati; Norisca Aliza Putriana; Silmi Auliya Zakariya (Jurnal Jamu Indonesia, 2022)
The COVID-19 pandemic caused by SARS-CoV-2 virus lead to massive death counts in parts of the world, including in Indonesia. Indonesian people often use herbal medicine as a way to increase their immune system, to prevent infection, and to accelerate the healing process of COVID-19. They are used to compose herbs with several medicinal plants as ingredients.  This review was aimed to provide information about immune booster herbs in Indonesia along with how to make it, its composition, its chemical contents, and how to use it in order to obtain scientific basis in understanding the efficacy and the herbal formulation. The method was carried out by browsing the literature from 2011-2021 through Google Scholar database from September 2021 to October 2021. The keywords used were "immune booster",  “immune boosting herbs”, “jamu”, “herbal ingredient”, “formulation” using the Boolean Operators 'AND' 'OR' and ‘NOT’. The literature that met the inclusion criteria were 30 journals. From the literature review, it was known that there are 22 species of medicinal plants that are used for 37 immune booster jamus with Zingiberaceae as the majority of the family (31%). The top ten plants commonly found in the ingredients are turmeric, ginger, lemongrass, temulawak, cinnamon, red ginger, lime, lesser galangal, meniran, and centella asiatica. Based on the plant’s chemical constituents, it was found that the secondary metabolites components which could potentially boost immunity are essential oils, flavonoids, saponins, tannins, and phenols. Meanwhile, the active compounds for immune booster were curcumin, gingerol, xanthorrhizol, citral, p-methoxycinnamate, and philanthine.